Catwoman - Pitof; Berry, Halle; Bratt, Benjamin, 1963-; Stone, Sharon, 1958-; Wilson, Lambert; Conroy, Frances; Arbogast, Thierry; Badelt, Klaus; Kane, Bob.; Warner Home Video (Firm) (Burbank, Calif. : Warner Home Video, 2005)
Sensitive and shy artist Patience Philips is a woman who can't seem to stop apologizing for her own existence. She works as a graphic designer for Hedare Beauty, a mammouth cosmetics company on the verge of releasing a revolutionary anti-aging product. When Patience inadvertently happens upon a dark secret her employer is hiding, she finds herself in the middle of a corporate conspiracy. What happens next changes Patience forever. In a mystical twist of fate, she is transformed into a woman with the strength, speed, agility and ultra-keen senses of a cat.
Title from disc.
Special features: alternate ending and additional scenes; 2 documentaries : "The many faces of 'Catwoman'" and "Behind the scenes"; DVD-ROM weblink to Catwoman's world.
Originally released as a motion picture in 2004.
Director of photography, Thierry Arbogast ; art directors, Dan Hermansen, Don Macaulay ; editor, Sylvie Landra ; music, Klaus Badelt ; costume designer, Angus Strathie ; production designer, Bill Brzeski ; visual effects supervisors, Scott Frankel ... [et al.] ; special effects director, Tony Lazarowich.
Halle Berry, Benjamin Bratt, Sharon Stone, Lambert Wilson, Frances Conroy, Alex Borstein, Michael Massee, Byron Mann, Kim Smith.
MPAA rating: PG-13; for action violence and some sensuality.
Keywords: Catwoman -- (Fictitious character) -- Drama; Cosmetics industry -- Drama; Aging -- Prevention -- Drama; Conspiracies -- United States -- Drama; Feature films; Video recordings for the hearing impaired